2016
DOI: 10.2147/prom.s115488
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the Oxford shoulder score and shoulder pain and disability index: factor structure in the context of a large randomized controlled trial

Abstract: BackgroundTo explore and compare the factor structure of the 12-item Oxford shoulder score (OSS) and 13-item shoulder pain and disability index (SPADI).MethodsExploratory factor analysis (EFA) and confirmatory factor analysis (CFA) of data from 660 patients attending 46 hospitals in the UK. Complete OSS and SPADI data were available for 648 (98.2%) and 628 (95.2%) participants, respectively.ResultsFor both instruments, either one or two factors were indicated, depending on the extraction method. On EFA, most O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…This concurs with findings from several factor analyses that have indicated that the SPADI has at least two dimensions (9,12). Recently, data on the SPADI and Oxford Shoulder Score collected in a large randomized controlled trial comparing shoulder surgery with rest and exercise were analysed using exploratory and confirmatory factor analysis (8). The fit of both one-and two-factor hypothesised models were assessed and the authors conclude that both a single factor 13-item structure and two-factor pain and disability structure are supported and that the SPADI pain and disability subscales are suitable as primary endpoints.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This concurs with findings from several factor analyses that have indicated that the SPADI has at least two dimensions (9,12). Recently, data on the SPADI and Oxford Shoulder Score collected in a large randomized controlled trial comparing shoulder surgery with rest and exercise were analysed using exploratory and confirmatory factor analysis (8). The fit of both one-and two-factor hypothesised models were assessed and the authors conclude that both a single factor 13-item structure and two-factor pain and disability structure are supported and that the SPADI pain and disability subscales are suitable as primary endpoints.…”
Section: Discussionsupporting
confidence: 83%
“…The SPADI is short, easy to complete and score and has been widely adopted and recommended for clinical practice and research (6,8,9). It has been studied in multiple contexts for its validity, reliability and responsiveness (6)(7)(8)(9)(10)(11)(12)(13); using classical test theory (CTT). However, recent developments in the field of psychometrics and the scientific requirements for use of PROMs in clinical trials have highlighted that ordinal rating scales often do not meet the criteria for true interval-level measurement (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…This is the likely reason why previous studies have reported more of a unidimensional structure for the SPADI, especially where the pain construct is very high in conditions such as in adhesive capsulitis [25, 26]. A recent large randomised control trial and a multi-centre cohort study have provided further evidence of a two-factor structure for the SPADI, but even these studies suggest that the two factors of pain and disability are not well delineated with some items cross-loading [27, 28] and misfit of the disability items when the Rasch model is used [28].…”
Section: Discussionmentioning
confidence: 99%
“…We chose a patient-reported outcome [40] which directly measures the participants' shoulder complaints. The OSS has been translated and cross-culturally adapted to Danish [19] and is a valid, reliable, and responsive shoulder-specific measure [17,[41][42][43][44]. It is one of the recommended first choice instruments in patients with shoulder disorders [45].…”
Section: Primary Outcomesmentioning
confidence: 99%